Uses and abuses of IMPLAN in economic impact studies of tourism events and facilities in the United States: a perspective article. Issue 1 (12th September 2019) - Crompton, John
Abstract : Purpose: An overview of the IMPLAN input/output model which is the dominant economic impact model used in the USA, focused on the ways it is abused. Design/methodology/approach: Review of the literature. Findings: 25 ways in which IMPLAN is abused. Research limitations/implications: Continued refinement of IMPLAN in the USA; potential of its extension to other contexts. Practical implications: Beware it is frequently used to confirm an advocacy position of those who commission studies, rather than a search for truth. Social implications: Profound potential for creating falsified outcomes to support sponsor advocacy. Originality/value: Synopsis of IMPLAN literature and identification of abuses.